A Digital-Based Practical Guide to Encourage Students' Critical Thinking Skills - Deni Yunita; Jayanti Syahfitri; Nopriyeni (Postgraduate, University of Mataram, 2025)
This research aims to develop a digital-based practicum guide to stimulate the critical thinking skills of high school students on cell structure materials. This research uses the 4D model development method (Define, Design, Develop, Disseminate), which consists of the stages of defining needs, product design, development, and dissemination. The product is developed in the form of an interactive flipbook that contains videos, images, critical thinking simulation questions, and answer links. The validation results showed that the digital-based practicum guide was declared very valid by media experts with a score of 97 and by material experts with a score of 95. The practicality test involving 74 students showed an average score of 90 in the